2019
DOI: 10.1182/blood.2018888107
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics inhibit tumor and disease activity in cutaneous T-cell lymphoma

Abstract: This paper reports that aggressive antibiotic treatment inhibits disease activity and lymphocyte proliferation in cutaneous T-cell lymphoma (CTCL). The study offers important evidence for a link between bacterial infection, activation of the immune system, and CTCL progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 37 publications
5
100
0
1
Order By: Relevance
“…It would be worth examining whether expression of other CE proteins is also downregulated by Th2 cytokines. Furthermore, the hypothesis of CTCL pathogenesis, concerning chronic antigen stimulation with bacterial superantigens such as S. aureus leading to the development and clonal proliferation of malignant T-cells seems to be up to date [4,[26][27][28][29]. In the resent study, Lindahl and coworkers reported inhibition of malignant T-cells and clinical improvement in patients with advanced-stage CTCL after antibiotic treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…It would be worth examining whether expression of other CE proteins is also downregulated by Th2 cytokines. Furthermore, the hypothesis of CTCL pathogenesis, concerning chronic antigen stimulation with bacterial superantigens such as S. aureus leading to the development and clonal proliferation of malignant T-cells seems to be up to date [4,[26][27][28][29]. In the resent study, Lindahl and coworkers reported inhibition of malignant T-cells and clinical improvement in patients with advanced-stage CTCL after antibiotic treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…[25] Current studies indicate that colonized SSAg-producing S. aureus intensify cutaneous inflammation of atopic dermatitis and Sézary syndrome and promote tumor progression in Sézary syndrome. [26,27] Antibiotics have an ameliorating effect on inflammation in these conditions, [28] [29] Oral antibiotics are also administered as a treatment for LyP. However, because LyP is a chronic condition characterized by intermittent flare ups of lesions, it is difficult to determine the long term effectiveness of anti-Staphylococcal antibiotics for LyP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further demonstrated that patients exhibiting clinical improvement after transient antibiotic therapy, display diminished STAT3 signaling, IL-2Rα expression and cell proliferation in the lesional skin (Lindahl et al, 2019). Antibiotic treatment not only reduced the disease activity at the clinical and histological level but also resulted in a significant decrease in the fraction of malignant T cells in the lesional skin in the majority of patients (Lindahl et al, 2019). These findings indicate that there may be a mutual sustenance between the malignant T cells and toxin-producing S. aureus where the former compromise the local immunity and the bacteria, in turn, mitigate anti-tumor responses while concurrently fueling the expansion of malignant T cells.…”
Section: Interactions Between Bacterial Toxins and Malignant T Cellsmentioning
confidence: 95%